Robustness of Sharing Rules under Climate Change - The Case of International Fisheries Agreements - Urs Steiner Brandt; Lone Grønbæk Kronbak (University of Southern Denmark, Department of Environmental and Business Economics (IME), 2006)
Many international fisheries agreements involve sharing rules. The current pa-per analysis the stability of sharing rules when coping with long run changes in the composition of fish stocks in an international setting due to climate change. The exploitation of the cod stock in the Baltic Sea serves as an illustrative ex-ample. These rules are normally stable rules, but this is only true if they are not contingent on shifts in the relative distribution of density of the resource. Given the projected climatic changes in the latest IPCC report the stability of these agreements is not guaranteed. The lack of robustness of management systems of shared fish stocks with respect to exogenous changes has been addressed in sev-eral papers (see e.g. Miller (2005) and Miller and Munro (2004)). This paper builds, however, on a more rigorous game theoretic analysis conducted by Kronbak and Lindroos (2005). The main findings of this paper is that, when ex-ternalities are present, a decrease in the resource rent implies that the threat for not free riding become less serious and thereby leave less room for stable solu-tion. Generally speaking, this implies that climatic changes with a negative ef-fect on the resource rent make joint solutions less likely.
Keywords: C62; C70; Q22; Q54; 330; Climate Change; Cooperative Games; Stability of Fisheries Agreements; Fischereirecht; Fischereiressourcen; Externer Effekt; Kooperatives Spiel; Theorie